Na batida do baião: o cavalo-marinho no terreiro da família Teles em Condado - PE - Alcântara, Paulo Henrique Lopes de (2014)
The cavalo-marinho, a traditional practice from the sugarcane region of Pernambuco, fuses music with aspects of dance, poetry, and drama to constitute a brilliant expression of sound and movement. Yet in recent years this playful activity has gained increasingly ample notoriety, primarily in urban spaces and within the industry of symbolic goods, as a means of social inclusion and cultural recognition. Emerging from within this context is the Teles family, a family comprising three generations of individuals who live, create, and recreate cavalo-marinho in the small city of Condado (Pernambuco), placing the past into dialogue with the present and signaling possible directions for the practice‟s future. As such, the present text seeks to advance an understanding of various aspects of cavalo-marinho‟s musical heritage, aiming to interpret the practice‟s continuities and current transformations by way of the experiences, discourses, practices, values, and conceptions of its creators and heirs.